Homeownership of Immigrants in France: Selection Effects Related to International Migration Flows - Laurent Gobillon; Matthieu Solignac (Institute for the Study of Labor (IZA), 2015)
We investigate the difference in homeownership rates between natives and first-generation immigrants in France, and how this difference evolves over the 1975-1999 period, by using a large longitudinal dataset. We find that the homeownership gap is large and has increased. Entries into the territory have a large negative effect on the evolution of homeownership rates for immigrants. Although entrants have on average better education than people staying in the territory for the entire period (i.e. stayers), they are younger and thus at an earlier stage in the wealth accumulation process. They are also located in large cities, where the homeownership rate is lower, and the returns to their characteristics are lower than those for stayers. Leavers have a positive effect on the evolution of homeownership rates for immigrants because they have a low access to homeownership and they exit the country. But this effect is only one-third that of entrants. For stayers, we show that returns to characteristics change in favor of immigrants, which is consistent with assimilation theories. However, among stayers who access homeownership, immigrants end up in owned dwellings that are of lesser quality than natives.
Keywords: J15; R21; 330; homeownership; immigrants; longitudinal data